How to measure educational environment of university? - Simkhovich, Valentina A. (Journal of the Belarusian State University. Sociology, 2022)
The article is devoted to the issue of evaluating the educational environment of a higher educational institution. The issue is of actual character since an optimal educational environment is one of the conditions for training competitive and competent specialists. University educational environment is specific as it purposefully affects the future specialist’s professional and personal development, ensures his readiness for professional activity, successful fulfillment of social roles and self-realisation in the process of life. In the article the educational environment of university is considered from the viewpoint of a competency-based approach wherein the subject-subject relations (teacher-student activity), educational goals and learning outcomes are treated as elements of the educational environment. Due to the fact that there are a few native methods of evaluating the educational environment of university, the DREEM methodology (Dundee Ready Educational Environment Measure) developed by the University of Dundee (UK) in 1997 and actively used by foreign medical universities is suggested to consider. A valid tool for evaluation is the DREEM questionnaire with the aim to identify the strengths and weaknesses of the university educational environment. Although the DREEM questionnaire requires some adjustment in terms of taking into account the realities of the national system of higher education, fields of training and the like, wordings of its questions are quite universal that makes it possible to use the given toolkit to evaluate the educational environment of Belarusian higher educational institutions training specialists in various fields.